THE GENOCIDE OF ARMENIANS: A VIEW FROM INSIDE AND OUTSIDE - Gasparyan, Naira H. (Armenian Folia Anglistika, 2025)
This research aims to provide a fresh perspective on the Armenian Genocide by examining eyewitness accounts, missionary reports based on factual evidence, and reflections from official humanist organizations dating back to the 1890s. The research applies various universal approaches, including Gregory H. Stanton's 10 stages of genocide and the Post-Traumatic Stress Disorder (PTSD) approach focusing on identity transformation, analysis of the linguistic material through consideration of extra-linguistic factors. The paper argues that global education on genocide, particularly the Armenian Genocide, is crucial for individuals to confront the truth and foster cooperation without animosity. This multidisciplinary study emphasizes that the condemnation of genocide by global organizations is a necessary human response, that genocidal behavior should be recognized as an established illegal stage, and that the terminology and narrative of genocide should be taught at the university level to achieve prevention. The study of the historical reality and linguistic material through implementing the cognitive-linguistic, linguo-stylistic and cultural-linguistic methods presupposes a careful text selection and juxtaposition. The article demonstrates how examining the conflict between old and modern viewpoints can advance genocide education and prevention. This constitutes the novelty of the research.
Keywords: Survivor accounts; missionary memoirs; identity; the Armenian Genocide; Stanton’s Genocide Stages; PTSD; global education